Psychosocial interventions for violence exposed youth: a systematic review - Lindert, Jutta U.; Jakubauskiene, Marija; Natan, Marta; Wehrwein, Annette; Bain, Paul; Schmahl, Christian; Kamenov, Kaloyan; Carta, Mauro; Cabello, Maria (Child abuse & neglect, 2020)
Background - Violence exposure (direct, indirect, individual, structural) affects youth mental health. - Objective - We aimed to evaluate the effectiveness of psychosocial interventions in addressing the sequelae of violence exposure on youth (15-24 years old) and evaluate whether moderating factors impact intervention effectiveness. - Methods - We systematically searched eight databases and reference lists to retrieve any studies of psychosocial interventions addressing mental health among youth aged 15-25 exposed to violence. We assessed study risk of bias using an adapted version of the Downs and Black’s Risk of Bias Scale. - Results - We identified n = 3077 studies. Sixteen articles representing 14 studies met were included. The studies assessed direct and indirect individual violence exposure at least once. We pooled the data from the 14 studies and evaluated the effects. We estimated an average effect of r+ = 0.57 (RCTs: 95 % CI 0.02-1.13; observational studies: 95 % CI 0.27-86) with some heterogeneity (RCTs: I2 = 78.03, longitudinal studies: I2 = 82.93). The most effective interventions are Cognitive Behavioral Therapy, and Exposure Therapy with an exposure focus. However, due to the small number of studies we are uncertain about benefits of interventions. - Conclusions - No study assessed structural violence. Therefore, studies are needed to evaluate the effects of psychosocial interventions for youth exposed to direct, indirect, individual and structural violence.